Os intelectuais orgânicos da base nacional comum curricular (BNCC): aspectos teóricos e ideológicos - Gonçalves, Amanda Melchiotti (2020)
A dissertation “The Intellectual Organs of the National Common Curricular Base (BNCC): Theoretical and Ideological Aspects”, developed at the State University of Western Paraná - UNIOESTE, campus of Cascavel / PR, in the line of “Education, Social Policies and State”, aims to analyze the production of the main BNCC Intellectual Organs that support theory and ideology as proposals adopted by the document. To develop, support documentary research, with an emphasis on documents: Common National Curriculum Base - Early Childhood Education and Elementary Education, 2017; Common National Base Curriculum - High School, 2018; World Bank - A 2018 skills and jobs agenda for youth; Education in four dimensions: The skills that students need to have success. The theoretical analysis support, consider the various determinations for understanding the historical movement of documents, as the premise is that these resources are related to the historical, political and economic period, in order to allow the confrontation of the objective reality of the facts. It was found, that covered a “new” paradigm, a BNCC translates an applied psychology for survival in the modern world of the 21st century. The concepts employed are not random, on the contrary, they refer to a globalizing education that reinforces the human formation process aimed at in the current form of capital's sociability, at the same time that it corroborates in the structural adjustment process of capital